Composite fabric and preparation method thereof
By using warp and weft interwoven and embossing processes in composite fabrics to form three-dimensional patterns, combined with caustic treatment and high-temperature hot pressing technology, the durability and bonding process difficulties of compression bag products in the existing technology are solved, and high-quality The improvement of fitting strength and peeling strength is suitable for the application of home products.
Patent Information
- Application Number
- CN202411579775.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-27
AI Technical Summary
The existing compression bag products are mainly made of plastic film, with poor user experience, insufficient durability, and the bonding process of composite fabrics is difficult and the peeling strength is insufficient, which cannot meet the needs of vacuum storage.
Using composite fabric composed of base fabric layer, adhesive layer and plastic film layer, three-dimensional patterns are formed through warp and weft interwoven and embossing processes, combining caustic treatment and high-temperature hot pressing technology to optimize yarn specifications and fabric structures, and improve patching Fitness and peel strength.
It achieves high fit strength and durability of composite fabrics, provides a balance of aesthetics and practicality, is suitable for applications such as compression bags, and has the characteristics of high strength and durability, and has a delicate and soft feel, which is suitable for home products.
Smart Images

Figure CN119189452A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite fabric and a preparation method thereof, belonging to the technical field of composite materials. Background Art
[0002] As people's pace of life accelerates, their requirements for quality of life continue to increase. Storage and organization have not only become a necessary ritual chore for people's daily lives, but have also improved the quality and taste of life. Therefore, storage products such as compression bags with a sense of quality are becoming more and more popular among consumers. Currently, compression bag products on the market are mostly made of plastic film, which is easy to store and store, but the plastic feel is too strong, the user experience is not good, and the strength of plastic is limited, resulting in the product not having good durability.
[0003] When people choose a product, they will not only consider its practicality and durability, but also be attracted and impressed by its comfort and fashion sense. The carved patterns are rich and colorful. Compared with the two-dimensional printed patterns, the carved patterns are more three-dimensional, with a sense of spatial depth and a stronger visual impact. At present, in the finishing process of textile fabrics, the embossing and burnt-out processes can achieve patterns with concave and convex effects. Among them, the burnt-out process causes huge loss of fabric strength, and is not suitable for products with high durability requirements. The embossing process causes relatively little damage to the fabric strength, and can take into account both aesthetics and practicality. However, the embossed fabric will inevitably bring about the unevenness of the fabric surface, thereby increasing the processing difficulty of the composite fabric bonding process. The bonding fastness of the textile composite fabric directly affects the durability and quality of the product.
[0004] There are many studies on improving the peel strength of composite fabrics in the market. For example, patent CN116278280A discloses a multifunctional composite fabric that is connected by hot-melt adhesive through a microporous membrane structure to form a relatively good peel strength between the fabric and the membrane. However, the airtight effect of the microporous membrane structure has certain limitations and is far from meeting the requirements of vacuum storage. Patent CN114714677A discloses a composite outdoor fabric and its manufacturing process. The film surface is treated with plasma to eliminate impurities and improve the peel strength between the fabric and the fabric. The patent does not mention the effect of improving the peel strength, and plasma treatment is not currently universal. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the prior art and provide a composite fabric with high bonding strength and strong durability. The composite fabric has obvious three-dimensional pattern effect and delicate and soft touch.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A composite fabric, consisting of a base fabric layer, an adhesive layer and a plastic film layer, characterized in that the base fabric layer is a fabric formed by interweaving warp and weft yarns with a denier of 50 to 300D, the surface of the composite fabric is divided into a pattern part and a flat part, and the difference in thickness between the pattern part and the flat part does not exceed 20μm. The warp and weft interweaving of the base fabric can be plain, double plain or square, and the pattern part is obtained by embossing, so the thickness of the pattern part is less than that of the flat part.
[0008] In the present invention, the thickness of the flat part of the base fabric layer is 0.16-0.37 mm, and the thickness of the pattern part is 0.16-0.35 mm.
[0009] Preferably, the warp and weft yarns are made of cationic polyester and ordinary polyester composite yarn, and the cationic polyester accounts for 33-67% of the composite yarn; further, the warp and weft yarns can also be made of only ordinary polyester yarns.
[0010] Preferably, the warp and weft yarns have the same specifications, and the F number of the warp and weft yarns is 72-336F.
[0011] Preferably, the base fabric layer has a grammage of 60 to 175 g / m 2 The preferred composite fabric weight is 115-275 g / m 2 .
[0012] Preferably, the plastic film layer is a PE film layer, a PA / PE composite film layer or a PA / PE co-extruded film layer, and the weight of the plastic film layer is 30 to 80 g / m 2 .
[0013] A method for preparing the above-mentioned composite fabric is characterized by comprising the following steps:
[0014] S1. Using selected warp and weft yarns to form a grey cloth on a water jet loom;
[0015] S2. Degreasing, causticizing, dyeing and shaping the grey cloth into colored fabric;
[0016] S3. The colored fabric is passed through a pattern roller and hot-pressed at high temperature to form a concave and convex pattern to obtain a base fabric layer;
[0017] S4. The base fabric layer is passed through a liquid roller with glue attached thereto, and the glue is applied to the non-embossed side of the base fabric layer, and then the base fabric layer and the plastic film are hot-pressed at high temperature to form a composite fabric;
[0018] S5. The composite fabric is rolled up under tension to form a tube.
[0019] Among them, in step S2, the degreasing process is 2-3g / L Na2CO3, the degreasing agent is 4-5g / L, the treatment is carried out at 90°C for 30min, and the fabric is rinsed once with hot water at 70°C; then the fabric is causticized, the causticization process is 4-7g / L NaOH, the temperature is rapidly raised to 100°C for 20min, the liquid is drained at 85°C, and the fabric is rinsed twice with hot water at 80°C.
[0020] In step S2, according to the fabric requirements, only the cationic polyester can be dyed to achieve a color spinning effect, or the cationic polyester and ordinary polyester can be dyed at the same time to achieve a pure color effect.
[0021] Among them, in step S3, the hot pressing temperature of the pattern is 185-205° C., the processing speed is 12-15 m / min, and the pressure is 1.5-2.5 kg.
[0022] Wherein, in step S4, the curing temperature of the base fabric layer and the plastic film layer during hot pressing is 100-110° C., the processing speed of bonding and curing is 3-10 m / min, and the pressure is 2-2.5 kg.
[0023] Among them, in step S5, the rolling tension of the composite fabric is: 15-30N, the rolling speed is: 5-10m / min, and the roll material needs to be left to stand for 8-12 hours at a temperature of 25-40°C and a humidity of 40-85% to ensure that the fabric and the film have the best fit.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The composite fabric of the present invention takes into account the contradiction between the aesthetics of the three-dimensional pattern effect of the composite fabric of the final product and the use strength by optimally setting the pattern part and the flat part of the base fabric layer. Through the optimal yarn count and fabric structure, the composite fabric has a uniform, delicate, soft and high-quality surface.
[0026] The present invention solves the peeling strength problem in the uneven fabric and film laminating process through a causticizing process, further improves the application of the composite fabric with concave and convex three-dimensional pattern as a composite film material for compression bags, and has the characteristics of high strength and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the cross-sectional structure of the present invention;
[0028] Figure 2 It is a schematic diagram of making a compression bag according to the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below through the accompanying drawings and specific embodiments.
[0030] like Figure 1-2 As shown, a composite fabric is composed of a base fabric layer 1, an adhesive layer 2 and 3 plastic film layers. The base fabric layer 1 is a concave-convex pattern layer interwoven with warp and weft yarns. The surface of the composite fabric is divided into a pattern part 100 and a flat part 200. The thickness difference between the pattern part 100 and the flat part 200 does not exceed 20 μm. The warp and weft interweaving method of the base fabric can be a single warp and single weft plain weave, a double plain weave or a square weave.
[0031] Preferably, the thickness of the flat part 200 is 0.16-0.37 mm, and the thickness of the pattern part 100 is 0.16-0.35 mm. The pattern part 100 and the flat part 200 are kept at the optimal thickness difference, in order to ensure that the fabric surface has a certain three-dimensional sense while also having a relatively uniform high strength. When the thickness difference between the pattern part and the flat part exceeds 20 μm, the corresponding pattern part is affected by a certain high temperature, resulting in a significant decrease in strength value, which affects the strength performance of the composite fabric.
[0032] Repeated experiments have shown that when the thickness difference between the pattern part and the flat part exceeds 20um, the strength value of the corresponding pattern part of the composite fabric decreases significantly, affecting the strength performance of the entire composite fabric. Under the process conditions of the same amount of glue, when the thickness difference between the pattern part and the flat part exceeds 20μm, the glue application on the flat part of the base fabric layer will be too little, and the peeling strength requirements of the composite fabric will not be met. At the same time, when the thickness difference exceeds 20μm, when the base fabric layer is hot-pressed at high temperature, the yarn extension of the pattern part is greater than that of the flat part, resulting in larger pores in the pattern part than in the flat part, and the contact area of the glue point becomes smaller, resulting in uneven glue application under the process conditions of the same amount of glue, and the peeling strength of the pattern part on the surface of the composite fabric will also be low, which ultimately leads to low peeling strength of the entire composite fabric.
[0033] Furthermore, a tissue structure with a balanced proportion in the warp and weft directions is preferred, so that in the gluing process, the glue dots can be evenly distributed on the warp and weft yarns, so that the bonding strength of the composite fabric will be higher.
[0034] The warp and weft yarns have the same specifications, with deniers of 50 to 300D and F numbers of 72 to 336F. The yarn should not exceed 300D, because the yarn is too thick, the gap between the interlacing points of the base fabric layer is too large, and the fabric surface is prone to glue penetration; the yarn should not be less than 50D, because the yarn is thin and the density is high, the fabric is too thin, and the composite fabric is easy to show the bottom.
[0035] Preferably, the warp and weft yarns are made of composite yarns of cationic polyester and ordinary polyester, and the proportion of cationic polyester in the composite yarn is 33-67%. In the subsequent printing and dyeing processing of the base cloth, the fabric needs to add a causticizing process, that is, the surface is hydrolyzed to make it rough. However, the glass transition temperature of cationic polyester is lower than that of ordinary polyester, and the cationic polyester has larger pores inside. Hydroxyl ions can more easily enter the cationic polyester for etching and hydrolysis, resulting in the strong damage of the cationic polyester becoming more obvious, which in turn affects the processing of hot-pressed patterns. The present invention meets the processing requirements of hot-pressed patterns by controlling the proportion of cationic polyester in the composite yarn. At the same time, with such a proportion, when single-dyeing cationic polyester, the fabric can have a very obvious two-color difference, and the color spinning effect is comparable to the fabric obtained by blending colored staple yarns, and the process is simpler and more durable.
[0036] Preferably, the weight of the base fabric layer is between 60 and 175 g / m 2 Furthermore, the weight of the composite fabric is between 115 and 275 g / m 2 The fabric weight is too low, the tightness of the fabric is too small, and the gaps between the filaments are large. When the pattern is hot-pressed, the filaments are easily slipped by external force, causing the fabric to be pierced, and the fabric surface is prone to glue penetration, affecting the overall quality of the composite material; when the fabric weight is too high, although there is no glue penetration, the hand feel is obviously hard, and the user experience becomes worse.
[0037] The plastic film layer is a PE film layer, a PA / PE composite film layer or a PA / PE co-extruded film layer, and the weight of the plastic film layer is 30 to 80 g / m 2 If the plastic film is too thin, the composite fabric will be easily damaged or have holes; if the plastic film is too thick, the composite fabric will feel too hard.
[0038] The present invention provides a method for preparing a composite fabric, comprising the following steps:
[0039] S1. Using selected warp and weft yarns to form a grey cloth on a water jet loom;
[0040] S2. The grey cloth is degreased, causticized, dyed, and shaped to form a colored fabric;
[0041] S3. The colored fabric is passed through a pattern roller and hot-pressed at high temperature to form a concave and convex pattern to obtain a base fabric layer;
[0042] S4. The base fabric layer is passed through a liquid roller with glue attached thereto, and the glue is applied to the non-embossed side of the base fabric layer, and then the base fabric layer and the plastic film are hot-pressed at high temperature to form a composite fabric;
[0043] S5. The composite fabric is rolled up under tension to form a tube, which needs to be left to stand for 8 to 12 hours at a temperature of 25 to 40°C and a humidity of 40 to 85% to ensure that the fabric and the film have the best fit.
[0044] Among them, in step S2, the degreasing process is 2-3g / L Na2CO3, the degreasing agent is 4-5g / L, the treatment is carried out at 90°C for 30min, and the fabric is rinsed once with hot water at 70°C; then the fabric is causticized, the causticization process is 4-7g / L NaOH, the temperature is rapidly raised to 100°C for 20min, the liquid is drained at 85°C, and the fabric is rinsed twice with hot water at 80°C.
[0045] The surface of the filament is relatively smooth. When the fabric and the film are glued together, the anchor point area of the film and the fabric is small, and the friction between the monofilaments in the yarn is also small, which easily causes slippage between the filaments, and ultimately leads to low peel strength between the film and the fabric. Although the present invention improves the specific surface area of the fabric by optimizing the design of the filament specifications and increasing the F number of the filament, thereby increasing the contact area between the fabric and the film during glue dispensing, this method is significantly improved compared to conventional monofilaments, but it is still far from expectations.
[0046] Furthermore, the present invention performs a causticizing treatment on the filaments, that is, a certain degree of hydrolysis and etching on the surface of the filaments, so that the surface of the filaments forms a rough surface with pits and bumps, which increases the contact area between the film and the fabric during glue dispensing on the one hand, and more importantly, increases the anchoring area between the glue and the surface of the filaments on the other hand. However, the causticizing treatment will hydrolyze the surface of the filaments, thereby causing certain damage to the strength of the filaments. At the same time, the causticizing process also causes the precipitation of hydrolysis products, which brings great problems and troubles to production and processing. In view of this problem, by controlling the temperature and time during causticizing, the temperature is quickly raised to a specific temperature, and the time required for slow heating is reduced. In this way, while meeting the peel strength of the glue dispensing film and the fabric, the damage effect of the causticizing process on the strength needs to be reduced as much as possible, thereby ensuring the strength of the subsequent hot pressing pattern process. The small molecule polymers after causticizing treatment can be well dissolved and dispersed in water in the form of colloids under a high temperature alkaline environment. In order to prevent these small molecule polymers from precipitating from water, the present invention designs high-temperature drainage and does not use neutralization treatment, thereby avoiding the small molecule polymers from being stained on the cloth surface to form dark spots.
[0047] Among them, in step S3, the hot pressing temperature of the pattern is 185-205°C, the processing speed is 12-15m / min, and the pressure is 1.5-2.5kg. By balancing the relationship between the hot pressing temperature, the speed and the pressure, a certain thickness difference of the concave-convex pattern is formed on the fabric. The fabric is higher than the glass transition temperature by about 90°C, and lower than the crystal melting temperature by about 235-240°C. It mainly acts on the amorphous area of the fiber, and the molecular chain segments produce internal rotation movement, adjust the molecular conformation, eliminate the local internal stress of the fiber, and increase the crystallization area in the fiber molecules. The concave-convex pattern formed is irreversible, so its pattern effect is relatively stable and permanent. After many experiments, it was found that such a thickness difference did not cause a significant reduction in the mechanical properties of the fabric. While ensuring the strength of the fabric, the composite fabric has a very exquisite three-dimensional pattern visual effect.
[0048] Wherein, in step S4, the curing temperature of the base fabric layer and the plastic film layer during hot pressing is 100-110° C., the processing speed of bonding and curing is 3-10 m / min, and the pressure is 2-2.5 kg.
[0049] When the above-mentioned base cloth with patterns is laminated, due to the uneven patterns on its surface, it is easy for the base cloth to be unable to be glued locally during glue application. Therefore, when the pressure is too small and the vehicle speed is too fast, the base cloth cannot form a good glue application, resulting in weak peeling strength. However, when the pressure is too large and the vehicle speed is too slow, the base cloth and the film are squeezed for a long time. Although they are fully laminated at this time, the original pattern is prone to deformation under this condition, resulting in unclear layering of the base cloth pattern. In order to reduce the mutual influence between vehicle speed and pressure, the present invention optimizes the speed and pressure of lamination curing to meet the peeling strength and base cloth pattern effect.
[0050] The embossed base fabric layer is glued to the plastic film, and the non-embossed side of the base fabric layer and the film are contacted with a liquid roller with glue attached, and are hot-pressed at high temperature to form a composite fabric.
[0051] In one embodiment, the composite fabric can be given different styles by changing the structure of the base fabric, the proportion of polyester to polyester, the warp and weft yarn counts, the base fabric weight, the base fabric and pattern thickness, the plastic film weight, and the glue weight.
[0052] The composite fabric of the present invention is further described below through specific examples and comparative examples.
[0053] The organizational parameters of Examples 1-9 (Examples 1-9) and Comparative Examples 1-6 (Comparative Examples 1-6) are shown in Table 1.
[0054] Table 1: The unit of weight is g / m 2 The proportion of cationic polyester is the mass proportion of cationic polyester in colored fabrics.
[0055]
[0056] The preparation methods of Examples 1-9 and Comparative Examples 1-6 are as follows.
[0057] Embodiment 1:
[0058] The yarn with a warp and weft count of 150D / 144F and a cationic polyester ratio of 33% was woven into a grey cloth according to a plain weave structure on a water jet loom; the grey cloth was treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90°C for 30min, rinsed once with hot water at 70°C, and then treated with 5g / L NaOH at 100°C for 20min, drained at 85°C, and rinsed twice with hot water at 80°C; cationic dyes were used to dye the cationic polyester to obtain a weight of 115g / m 2 , a color-spun fabric with a thickness of 0.246mm; the color-spun fabric is passed through a pattern roller, the hot pressing temperature is 190℃, the processing speed is 13m / min, the pressure is 2kg, and a pattern with a thickness of 0.24mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.006mm; the base fabric layer is attached with 10g / m 2 Glue-coated roller, with 60g / m 2 The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 20N and a rolling speed of 8m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0059] Embodiment 2:
[0060] The yarn with warp and weft count of 75D / 72F and cathodic polyester accounting for 50% was woven into grey cloth according to the plain weave structure on a water jet loom; the grey cloth was treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then treated with 4g / L NaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; cationic dyes were used to dye the cathodic polyester to obtain a weight of 80g / m 2 , a color-spun fabric with a thickness of 0.246mm; the color-spun fabric is passed through a pattern roller, the hot pressing temperature is 190℃, the processing speed is 13m / min, the pressure is 2kg, and a pattern with a thickness of 0.24mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.006mm; the base fabric layer is attached with 5g / m 2 Glue-coated roller, with 30g / m 2The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 15N and a rolling speed of 10m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0061] Embodiment 3:
[0062] The yarn with warp and weft count of 300D / 336F and cathodic polyester accounting for 67% was woven into grey cloth on a water jet loom according to a square weave structure; the grey cloth was treated with 3g / L Na2CO3 and 5g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then treated with 7g / L NaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; cationic dyes were used to dye the cathodic polyester to obtain a weight of 153g / m 2 , a color-spun fabric with a thickness of 0.36mm; the color-spun fabric is passed through a pattern roller, the hot pressing temperature is 190℃, the processing speed is 12m / min, the pressure is 2.2kg, and a pattern with a thickness of 0.348mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.012mm; the base fabric layer is attached with 15g / m 2 Glue-coated roller, with 30g / m 2 The plastic film is hot-pressed at high temperature to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 25N and a rolling speed of 6m / min, and left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0063] Embodiment 4:
[0064] The yarn with warp and weft count of 150D / 144F and cationic polyester accounting for 50% was woven into a grey cloth according to a plain weave structure on a water jet loom; the grey cloth was treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then causticized with 5g / LNaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; at the same time, the cationic polyester and ordinary polyester were dyed to obtain a weight of 115g / m 2 , a solid color fabric with a thickness of 0.246mm; the solid color fabric is passed through a pattern roller, the hot pressing temperature is 190℃, the processing speed is 13m / min, the pressure is 2kg, and a pattern with a thickness of 0.24mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.006mm; the base fabric layer is attached with 20g / m 2 Glue-coated roller, with 60g / m 2The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 20N and a rolling speed of 8m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0065] Embodiment 5:
[0066] The yarn with warp and weft count of 300D / 336F and cationic polyester accounting for 50% was woven into a grey cloth according to the plain weave structure on a water jet loom; the grey cloth was treated with 3g / L Na2CO3 and 5g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then causticized with 7g / LNaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; at the same time, the cationic polyester and ordinary polyester were dyed to obtain a weight of 153g / m 2 , a solid color fabric with a thickness of 0.37mm; the solid color fabric is passed through a pattern roller, the hot pressing temperature is 205℃, the processing speed is 12m / min, the pressure is 2.5kg, and a pattern with a thickness of 0.35mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.020mm; the base fabric layer is attached with 18g / m 2 Use the glue roller to apply glue on the base fabric, and then coat the base fabric layer with 60g / m 2 The plastic film is hot-pressed at high temperature to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 25N and a rolling speed of 6m / min, and left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0067] Embodiment 6:
[0068] The yarn with warp and weft count of 150D / 144F and cationic polyester accounting for 50% was woven into a grey cloth according to a plain weave structure on a water jet loom; the grey cloth was treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then causticized with 5g / LNaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; at the same time, the cationic polyester and ordinary polyester were dyed to obtain a weight of 115g / m 2 , a solid color fabric with a thickness of 0.246mm; the solid color fabric is passed through a pattern roller, the hot pressing temperature is 190℃, the processing speed is 13m / min, the pressure is 2kg, and a pattern with a thickness of 0.24mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.006mm; the base fabric layer is attached with 10g / m 2Use the glue roller to apply glue on the base fabric, and then coat the base fabric layer with 80g / m 2 The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 20N and a rolling speed of 8m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0069] Embodiment 7:
[0070] The yarn with warp and weft count of 300D / 336F and cationic polyester accounting for 67% was woven into grey cloth on a water jet loom according to the weft weight plain structure; the grey cloth was treated with 3g / L Na2CO3 and 5g / L degreasing agent at 90℃ for 30min, rinsed once with hot water at 70℃, and then causticized with 7g / LNaOH at 100℃ for 20min, drained at 85℃, and rinsed twice with hot water at 80℃; cationic polyester and ordinary polyester were dyed at the same time to obtain a solid color fabric with a gram weight of 149g / m2 and a thickness of 0.34mm; the solid color fabric was passed through a pattern roller, the hot pressing temperature was 190℃, the processing speed was 12m / min, and the pressure was 2.1k g, forming a pattern with a thickness of 0.328mm to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0.012mm; the base fabric layer is brought into contact with a liquid roller with 15g / m2 glue attached, and is hot-pressed with a 30g / m2 plastic film at high temperature to form a composite fabric; the composite fabric is rolled up at a rolling tension of 25N and a rolling speed of 6m / min to form a roll, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fitting fastness.
[0071] Embodiment 8:
[0072] The warp and weft yarn counts were 50D / 72F, and ordinary polyester filaments were woven into grey fabrics according to the plain weave structure on a water jet loom; the grey fabrics were treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90°C for 30min, rinsed once with hot water at 70°C, and then causticized with 4g / L NaOH at 100°C for 20min, drained at 85°C, and rinsed twice with hot water at 80°C; at the same time, the ordinary polyester was dyed to obtain a weight of 60g / m 2 , a solid color fabric with a thickness of 0.195mm; the solid color fabric is passed through a pattern roller, the hot pressing temperature is 185℃, the processing speed is 15m / min, the pressure is 1.5kg, and a pattern with a thickness of 0.195mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0mm; the base fabric layer is attached with 15g / m 2 Glue-coated roller, with 60g / m 2The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 15N and a rolling speed of 10m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0073] Embodiment 9:
[0074] The warp and weft yarn counts were 50D / 72F, and ordinary polyester filaments were woven into grey fabrics according to the plain weave structure on a water jet loom; the grey fabrics were treated with 2g / L Na2CO3 and 4g / L degreasing agent at 90°C for 30min, rinsed once with hot water at 70°C, and then causticized with 4g / L NaOH at 100°C for 20min, drained at 85°C, and rinsed twice with hot water at 80°C; at the same time, the ordinary polyester was dyed to obtain a weight of 60g / m 2 , a solid color fabric with a thickness of 0.160mm; the solid color fabric is passed through a pattern roller, the hot pressing temperature is 185℃, the processing speed is 15m / min, the pressure is 1.5kg, and a pattern with a thickness of 0.160mm is formed to obtain a base fabric layer, wherein the thickness difference between the flat part and the pattern part is 0mm; the base fabric layer is attached with 10g / m 2 Glue-coated roller with 40g / m 2 The plastic film is subjected to high temperature hot pressing to form a composite fabric; the composite fabric is rolled into a tube at a rolling tension of 15N and a rolling speed of 10m / min, and is left to stand for 10 hours at a temperature of 30°C and a humidity of 75% to ensure that the fabric and the film have the best fit.
[0075] Comparative Example 1:
[0076] Comparative Example 1 was carried out with reference to Example 1, except that the embossing process pressure was changed to 2.6 kg.
[0077] Comparative Example 2:
[0078] Comparative Example 2 was carried out with reference to Example 1, except that the amount of NaOH in the causticizing process was changed to 8 g / L.
[0079] Comparative Example 3:
[0080] Comparative Example 3 was carried out with reference to Example 1, except that the amount of NaOH in the causticizing process was changed to 3 g / L.
[0081] Comparative Examples 4-5:
[0082] Comparative Examples 4 and 5 were prepared according to the method of Example 3.
[0083] Comparative Example 6:
[0084] Comparative Example 6 was prepared according to the method of Example 2.
[0085] The examples 1-9 and the comparative examples 1-6 were tested. The tensile breaking strength of the composite fabric was tested according to the standard GB / T1040-1992 plastic tensile performance test method, and the peeling strength was tested according to the method of composite film A in the standard GB / T 8808-1988 soft composite plastic material peeling test method. The puncture strength was tested according to the standard GB / T 37841-2019 plastic film and sheet puncture resistance test method. The test results are shown in Table 2.
[0086] Table 2:
[0087]
[0088] It can be seen from the test results that in Example 1, the embossing is too heavy, resulting in reduced strength and puncture force of the composite fabric; in Example 2, the dosage of NaOH in the causticizing process is increased, and the fiber is excessively dissolved, resulting in reduced strength and easy peeling of the composite fabric; in Example 3, the dosage of NaOH in the causticizing process is reduced, the binding sites of the fiber and the dye are reduced, and the cloth surface and the film are easily separated; in Example 4, the organizational structure of the base fabric is changed, resulting in easy peeling of the film and the base fabric of the composite fabric; the yarn count of Example 5 is too coarse, and although the physical properties are slightly improved, the hand feel is hard, the fabric texture is rough, and there is serious "glue penetration", the fabric surface is shiny, and the plastic feel is strong; the yarn count of Example 6 is too fine, the composite fabric is too thin, the physical performance indicators are significantly reduced, and the fabric surface has a "bottom exposed" phenomenon.
[0089] The composite fabric obtained by the present invention has excellent peel strength (peel strength>6N) and excellent puncture resistance (puncture strength>25N). Compared with conventional films (puncture force of about 10-15N), the composite fabric is stronger and more durable. The fabric and the film have good fitting strength. The composite fabric has a uniform and delicate surface, a comfortable hand feel, no plastic feel, and a strong sense of quality, and is suitable for the application and promotion of household products.
[0090] Examples 1-9 are all feasible implementation plans within the technical requirements of the present invention.
[0091] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0092] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A composite fabric, consisting of a base fabric layer, an adhesive layer and a plastic film layer, characterized in that The base fabric layer is a fabric formed by interweaving warp and weft yarns of 50 to 300D. The surface of the composite fabric is divided into a patterned part and a flat part. The thickness difference between the patterned part and the flat part does not exceed 20 μm. The warp and weft yarns of the base fabric are interwoven in a plain weave, a double plain weave or a square weave.
2. A composite fabric according to claim 1, characterized in that The thickness of the flat part is 0.16-0.37 mm, and the thickness of the patterned part is 0.16-0.35 mm.
3. A composite fabric according to claim 1, characterized in that The warp and weft yarns are made of cationic polyester and common polyester composite yarn, and the cationic polyester accounts for 33-67% of the composite yarn.
4. A composite fabric according to claim 1, characterized in that The warp and weft yarns are made of common polyester yarns.
5. A composite fabric according to claim 1, characterized in that The warp and weft yarns have the same specifications, and the F number of the warp and weft yarns is 72F-336F.
6. A composite fabric according to claim 1, characterized in that The base fabric layer has a grammage of 60 to 175 g / m 2 .
7. A composite fabric according to claim 6, characterized in that The composite fabric has a grammage of 115 to 275 g / m 2 .
8. The composite fabric according to claim 1, characterized in that The plastic film layer is a PE film layer, a PA / PE composite film layer or a PA / PE co-extruded film layer, and the average gram weight of the plastic film layer is 30 to 80 g / m 2 .
9. A method for preparing the composite fabric according to any one of claims 1 to 8, characterized in that The following steps are involved: S1. Use selected warp and weft yarns to interweave on a water jet loom to form a grey fabric S2. Degreasing, causticizing, dyeing and shaping the grey cloth into colored fabric; S3. The colored fabric is passed through a pattern roller and hot-pressed at high temperature to form a concave and convex pattern to obtain a base fabric layer; S4. The base fabric layer is passed through a liquid roller with glue attached thereto, and the glue is applied to the non-embossed side of the base fabric layer, and then the base fabric layer and the plastic film are hot-pressed at high temperature to form a composite fabric; S5. The composite fabric is rolled up under tension to form a tube.
10. The method for preparing a composite fabric according to claim 9, characterized in that In step S2, the degreasing process is 2-3 g / L Na2CO3, the degreasing agent is 4-5 g / L, the treatment is carried out at 90°C for 30 min, and the fabric is rinsed once with hot water at 70°C; then the fabric is subjected to causticizing treatment, the causticizing process is 4-7 g / L NaOH, the temperature is rapidly raised to 100°C for treatment for 20 min, the liquid is discharged at a high temperature of 85°C, and the fabric is rinsed twice with hot water at 80°C.
11. The method for preparing a composite fabric according to claim 9, characterized in that In the step S3, the hot pressing temperature of the pattern is 185-205°C, the processing speed is 12-15m / min, and the pressure is 1.5-2.5kg; in the step S4, the curing temperature of the base fabric layer and the plastic film layer during hot pressing is 100-110°C, the processing speed of the bonding and curing is 3-10m / min, and the pressure is 2-2.5kg; in the step S5, the rolling tension of the composite fabric is 15-30N, the rolling speed is 5-10m / min, and the roll material needs to be left to stand for 8-12 hours at a temperature of 25-40°C and a humidity of 40-85%.
Citation Information
Patent Citations
Composite outdoor fabric and manufacturing process thereof
CN114714677A
Two-layer composite material of disposable surgical drape, and preparation method thereof
CN106945353A
Warp knitted fabric and dyeing and finishing process and fabric thereof
CN118581632A
Positive ion fabric structure
CN204039623U
Fabric with patterns
CN207088634U
